Controlled assembly of organic whispering-gallery-mode microlasers as highly sensitive chemical vapor sensors - Gao, Miaomiao; Wei, Cong; Lin, Xianqing; Liu, Yuan; Hu, Fengqin; Zhao, Yong Sheng (Chemical communications (Cambridge, England), 2017)
We demonstrate the fabrication of organic high Q active whispering-gallery-mode (WGM) resonators from π-conjugated polymer by a controlled emulsion-solvent-evaporation method, which can simultaneously provide optical gain and act as an effective resonant cavity. By measuring the shift of their lasing modes on exposure to organic vapor, we successfully monitored the slight concentration variation in the chemical gas. These microlaser sensors demonstrated high detection sensitivity and good signal repeatability under continuous chemical gas treatments. The results offer an effective strategy to design miniaturized optical sensors.